Functional identification of saline-alkali stress enhancing gene GATL1 in apple (Malus halliana) - Xiu Wang; Juanli Li; Zhongxing Zhang; Yanxiu Wang (Fruit Research)
Pectin is an essential component of the plant cell wall and is critical for maintaining the structural integrity of the plant and protecting it from biotic and abiotic stresses. Galacturonosyltransferase-like (GATL), a crucial enzyme within the pectin synthesis route, governs the biosynthesis and accumulation of pectin. In this study, MhGATL1, cloned from Malus halliana, was significantly upregulated under saline-alkali stress conditions. The MhGATL1 gene was transformed into Arabidopsis, tobacco, and apple callus through Agrobacterium-mediated transformation to obtain transgenic materials. Their tolerance to saline-alkali stress was appraised through various physiological and biochemical assays. Meanwhile, the yeast two-hybrid (Y2H) approach was adopted to identify and corroborate the interacting proteins. The results revealed that transgenic plants exhibited superior growth under stress conditions, as manifested by increased pectin content, elevated levels of chlorophyll and proline, enhanced activities of antioxidant enzymes (SOD, POD, CAT), decreased conductivity and MDA content, and a more favorable Na+/K+ ratio in comparison to wild-type plants. Furthermore, genes related to salinity stress and key pectin synthesis pathway genes were significantly upregulated in the overexpression lines compared to the wild type. Y2H experiments further demonstrated that MhGATL1 interacts with several proteins, including MhbZIP23, MhSOS2, MhUGE5, MhABI3, and MhCHI. These results suggest that MhGATL1 positively regulates plant saline-alkali tolerance. Thus, this gene holds great promise as a useful genetic resource for the development of apple varieties with enhanced tolerance to saline-alkali conditions.